2023
DOI: 10.1101/2023.03.31.23287853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Proteome Variation and its Genetic Determinants in Children and Adolescents

Abstract: The levels of specific proteins in human blood are the most commonly used indicators of potential health-related problems. Understanding the genetic and other determinants of the human plasma proteome can aid in biomarker research and drug development. Diverse factors including genetics, age, sex, body mass index (BMI), growth and development including puberty can affect the circulating levels of proteins. Affinity-based proteomics can infer the relationship between blood protein levels and these factors at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In our experience, unbiased proteomics usually results in panels of biomarkers that individually have small fold-changes but in combination capture sufficient information in body fluid proteomes to resolve confounders and accurately diagnose disease states. This empirical finding is supported by the notion that the body fluid proteome is multi-dimensional and influenced by factors such as genetics ( 91 , 92 , 93 , 94 ), gender ( 91 ), age ( 95 ), lifestyle ( 92 , 96 ), prior disease or treatment ( 97 ) and that biomarker panels are inherently better suited for to resolve this complexity ( 2 ). Our recent experience furthermore suggests that these panels typically comprised 10 to 20 proteins that together allowed patient classification ( 16 , 17 , 18 , 19 ).…”
Section: Lessons Learned In Recent Biomarker Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…In our experience, unbiased proteomics usually results in panels of biomarkers that individually have small fold-changes but in combination capture sufficient information in body fluid proteomes to resolve confounders and accurately diagnose disease states. This empirical finding is supported by the notion that the body fluid proteome is multi-dimensional and influenced by factors such as genetics ( 91 , 92 , 93 , 94 ), gender ( 91 ), age ( 95 ), lifestyle ( 92 , 96 ), prior disease or treatment ( 97 ) and that biomarker panels are inherently better suited for to resolve this complexity ( 2 ). Our recent experience furthermore suggests that these panels typically comprised 10 to 20 proteins that together allowed patient classification ( 16 , 17 , 18 , 19 ).…”
Section: Lessons Learned In Recent Biomarker Studiesmentioning
confidence: 88%
“…Similarly, identification of genetic effects on protein levels in body fluids termed protein quantitative trait loci (pQTL) typically requires large study collectives ( 113 ). In MS-based proteomics, larger study sizes have drastically raised the number of identified pQTLs and there is a higher pQTL identification rate compared to similar affinity binder proteomics studies ( 94 ).
Fig.
…”
Section: The Case For Large Better Characterized and Independent Cohortsmentioning
confidence: 99%
“…Participant genotyping was carried out as described previously (64,65). Out of the 1703 included participants, 1379 had been genotyped.…”
Section: Genotypingmentioning
confidence: 99%
“…Finally, we aimed to replicate our analyses by training models using data generated by a different proteomics technology. We therefore, as above, retrained models using a Danish cohort of obese children measured using mass spectrometry based (MS) proteomics (The HOLBAEK Study) 10 .…”
Section: Validating Discovery Of Non-linear Effects Using Mass Spectr...mentioning
confidence: 99%